Concurrent validity and test-retest reliability of a global positioning system (GPS) and timing gates to assess sprint performance variables - Waldron, M.; Worsfold, P.; Twist, C.; Lamb, K. (Journal of Sports Sciences, 2011)
There has been no previous investigation of the concurrent validity and reliability of the current 5 Hz global positioning system (GPS) to assess sprinting speed or the reliability of integrated GPS-accelerometer technology. In the present study, we wished to determine: (1) the concurrent validity and reliability of a GPS and timing gates to measure sprinting speed or distance, and (2) the reliability of proper accelerations recorded via GPS-accelerometer integration. Nineteen elite youth rugby league players performed two over-ground sprints and were simultaneously assessed using GPS and timing gates. The GPS measurements systematically underestimated both distance and timing gate speed. The GPS measurements were reliable for all variables of distance and speed (coefficient of variation [CV] = 1.62% to 2.3%), particularly peak speed (95% limits of agreement [LOA] = 0.00 ± 0.8 km/h; CV = 0.78%). Timing gates were more reliable (CV = 1% to 1.54%) than equivalent GPS measurements. Accelerometer measurements were least reliable (CV = 4.69% to 5.16%), particularly for the frequency of proper accelerations (95% LOA = 1.00 ± 5.43; CV = 14.12%). Timing gates and GPS were found to reliably assess speed and distance, although the validity of the GPS remains questionable. The error found in accelerometer measurements indicates the limits of this device for detecting changes in performance.